Dietary Strategies to Improve Cardiovascular Health: Focus on Increasing High-Density Lipoprotein Functionality - Stadler, Julia T.; Marsche, Gunther (Frontiers in Nutrition, 2021)
Cardiovascular disease is one of the leading causes of morbidity and mortality worldwide, with increasing incidence. A cornerstone of cardiovascular disease prevention is lifestyle modification through dietary changes to influence various risk factors such as obesity, hypertension and diabetes. The effects of diet on cardiovascular health are complex. Some dietary components and metabolites directly affect the composition and structure of high-density lipoproteins (HDL) and increase anti-inflammatory and vasoprotective properties. HDLs are composed of distinct subpopulations of particles of varying size and composition that have several dynamic and context-dependent functions. The identification of potential dietary components that improve HDL functionality is currently an important research goal. One of the best-studied diets for cardiovascular health is the Mediterranean diet, consisting of fish, olive oil, fruits, vegetables, whole grains, legumes/nuts, and moderate consumption of alcohol, most commonly red wine. The Mediterranean diet, especially when supplemented with extra virgin olive oil rich in phenolic compounds, has been shown to markedly improve metrics of HDL functionality and reduce the burden, or even prevent the development of cardiovascular disease. Particularly, the phenolic compounds of extra virgin olive oil seem to exert the significant positive effects on HDL function. Moreover, supplementation of anthocyanins as well as antioxidants such as lycopene or the omega -3 fatty acid eicosapentaenoic acid improve parameters of HDL function. In this review, we aim to highlight recent discoveries on beneficial dietary patterns as well as nutritional components and their effects on cardiovascular health, focusing on HDL function.